Sleep disturbance and associated factors among Nigerian adults living with HIV in the dolutegravir era - Osiyemi, Adenekan O.; Owoaje, Eme; Mundt, Jennifer M.; Oladeji, Bibilola; Awolude, Oluwatosin; Ogunniyi, Adesola; Okonkwo, Prosper; Berzins, Baiba; Taiwo, Babafemi O. (Frontiers in Sleep, 2022)
Sleep disturbance is common among persons living with HIV (PLWH) causing significant health impacts. Nigeria recently switched from efavirenz to dolutegravir (DTG) for first-line antiretroviral therapy (ART). This study aimed to assess the prevalence of sleep disturbance and to determine factors associated with sleep disturbance among treatment-experienced PLWH. Using a cross-sectional study design and systematic random sampling, 300 participants were recruited from the Infectious Diseases Institute, Ibadan, Nigeria (IDI). Interviewer administered questionnaire was used to collect data regarding sociodemographic, sleep disturbance (Pittsburgh Sleep Quality Index; PSQI), depression (Patient Health Questionnaire; PHQ-9), anxiety (Generalized Anxiety Disorder-7; GAD-7), and psychoactive substance use. HIV-specific data were retrieved from IDI’s medical records. The relationship between the PSQI score and the scores on the PHQ-9 and GAD-7 were explored with the Pearson correlation coefficient. Chi-square global tests of independence were used to assess factors associated with sleep disturbance and a multivariable binary logistic model was used to determine independent predictors of sleep disturbance. The mean age of the sample was 44.5 ± 11.4 (years), the average duration of HIV diagnosis was 8.13 ± 5.33 (years) and the majority were on DTG-based regimens (95%). Depression and anxiety were present in 14% and 17.3%, respectively. Prevalence of sleep disturbance (PSQI score of 6 or more) was 21.7%. Higher PSQI scores were associated with higher PHQ-9 scores (r = 0.526; p < 0.001) and higher GAD-7 scores (r=0.529; p<0.001). Sleep disturbance was associated with age (2 4.483, p = 0.038), marital status (2 7.187, p<0.01), depression (2 46.589, p<0.001) and anxiety (2 38.379, p<0.001). There was no significant association between sleep disturbance and HIV clinical stage at diagnosis, virological suppression status, and ART regimen type (p>0.05), whereas tea intake was associated with an absence of sleep disturbance (2 6.334, p<0.014). Age (>45years), depression and anxiety were associated with higher odds of sleep disturbance among PLWH. Sleep disturbance remains common among PLWH in the DTG era. Depression and anxiety are significant factors associated with sleep disturbance. Assessing these factors in future studies may improve the sleep health of PLWH.